The Role of Job Satisfaction in Mediating Organizational Culture and Work Life Balance on the Performance of Health Workers - Putu Santy Erawati; Ni Ketut Dewi Irwanti; Ni Luh Putu Agustini Karta (GLOBAL HEALTH SCIENCE GROUP, 2026)
Healthcare workers' performance is a crucial factor in ensuring service quality and patient safety in hospitals. This study aimed to analyze the effects of organizational culture and work-life balance on healthcare workers' performance, with job satisfaction serving as a mediating variable at Bali Mandara Eye Hospital. This study employed a quantitative approach with an explanatory research design. The respondents consisted of 115 civil servant healthcare workers used proportionate stratified random sampling, including physicians, nurses, and other healthcare professionals. Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The results indicated that organizational culture had a positive and significant effect on job satisfaction (β = 0.391; p < 0.05), as did work-life balance (β = 0.488; p < 0.05). Job satisfaction also had a positive and significant effect on healthcare workers' performance (β = 0.686; p < 0.05). In contrast, organizational culture and work-life balance did not have significant direct effects on healthcare workers' performance. Mediation analysis revealed that job satisfaction fully mediated the relationship between organizational culture and performance (β = 0.268; p < 0.05), as well as the relationship between work-life balance and performance (β = 0.335; p < 0.05). This study concludes that improving healthcare workers' performance can be achieved more effectively through enhancing job satisfaction, supported by a positive organizational culture and the implementation of a good work-life balance.